Eco-friendly and sustainable processing of wood-based materials. Issue 6 (12th March 2021) - Akpan, Emmanuel Isaac; Wetzel, Bernd; Friedrich, Klaus
Abstract : Eco-friendly alternative processes are required for functionally modified wood to maintain low embodied energy and near zero emission levels. Abstract : The hierarchical, porous, and macromolecular structures of woods provide opportunities for them to be modified and processed into structural, functional, and multi-functional materials. Chemical and thermal modifications are usually applied to adapt the wood structure and impart necessary functionalities. Most of these treatments use substantial amounts of chemicals, energy, and water. They also innocently incorporate unwanted chemically bonded structures into the wood and generate a large amount of waste products which are harmful to the environment. This brings a dilemma where an entirely sustainable and green material is converted to a non-environmentally friendly material. In this review, we provide an extensive analysis of the current modification techniques, chemicals and other raw materials from the perspective of sustainability, renewability, clean and cost-effective energy use, and overall compliance to the principles of green and sustainable chemistry. Alternative and prospective materials and methods which are environmentally sustainable, energy efficient, and cost effective are proposed.